A Study on the Construction and Dynamic Evolution of a Chinese Science and Technology Finance Index - Qingguo Zhang (Economies)
This study addresses regional disparities and the dynamic evolution of China’s science and technology finance integration (STFI) by constructing a composite index system using the entropy method. Recognizing the limitations of subjective weighting in traditional assessment frameworks, the entropy approach was employed to objectively quantify the contribution weights of 23 indicators across four dimensions: capital investment intensity, market development level, technological innovation efficiency, and public service accessibility. Analysis of panel data from 31 provinces (2010–2020) reveals three key findings: (1) China’s overall STFI exhibits a declining trend, with market development and capital investment emerging as primary drivers; (2) regional disparities are widening, as evidenced by a 2.3-fold increase in the coefficient of variation, with northwestern provinces demonstrating the fastest growth, while southwestern regions lag significantly; and (3) public services and innovation contributions remain underdeveloped, accounting for only 15.6% of the composite index. The entropy-based assessment framework demonstrates superior discriminatory power compared to principal component analysis, particularly in capturing regional heterogeneity. Policy implications include calls for intergovernmental coordination mechanisms, national market unification, inclusive service diffusion strategies, and targeted innovation investments. This research contributes a novel quantifiable tool for evaluating technology–finance synergies while highlighting systemic inefficiencies in China’s innovation-driven development paradigm.